Analisis Peran Pemerintah Desa Dalam Pemberdayaan Masyarakat Desa Tunahan Kecamatan Keling Kabupaten - suharto suharto (SOSIO DIALEKTIKA, 2024)
Community empowerment is a process carried out by the village government in increasing the dignity of the community so that it is able to make the community self-sufficient. With the existence of a program of community empowerment activities carried out by the village government for the community, it is hoped that it can improve the welfare of the community's standard of living and economy. However, the empowerment program implemented by the Tunahan Village government was not optimal. This study aims to find out the role of the village government as a regulator, catalyst, facilitator and dynamist in community empowerment, especially the farming community in Tunahan Village, Keling District, Jepara Regency. This study uses a descriptive qualitative research method, where research is carried out by field research, namely collecting information directly about a phenomenon that actually occurs in society and the community environment. Data were analyzed using in-depth interview techniques with village government and communities, direct field observations, and documentation. The results of this study are that the role of the Tunahan Village Government in community empowerment is quite good even though it is not optimal in the role of a catalyst, facilitator, and dynamicator in terms of the lack of attention from the village government in capital assistance provided to the community, the implementation of training programs provided by the Tunahan Village Government to the community still not intensive, and lack of community participation because the village is less able to influence or mobilize the involvement of community groups in every activity. There are factors that trigger this, namely supporting factors including leadership and strength, limitations, limitations and inhibiting factors including low skills and availability of facilities.